THE EFFECT OF SNOWBALL THROWING METHOD ON STUDENTS’ VOCABULARY MASTERY - Nina Haida Hasanah; Ashari P. Swondo (Universitas Potensi Utama, 2021)
This study was aimed to find the empirical evidence of the effect of Snowball Throwing Method on students’ vocabulary mastery. The method that was used was a quantitative method. The design of this study was experimental study. This study was conducted in MTS AL-IMAM KLUMPANG. The number of the sample of the study was 40 students of seventh grade. The instrument of this study was tests. The tests were divided into two, there were pre-test and post-test. The data that were obtained from the tests were analysed by using SPSS 20 program. The result of the study showed that the mean score of post test in control class was 66,5 while the mean score of post-test in experimental was 80 .Based on the criteria of hypothesis test that if sig. 2 tailed (p) was lower than alpha (α) 0.05, then Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. In this study, the result of sig. 2 tailed was 0.000 and it proved that p <α. It showed that there was a significant effect of Snowball Throwing method on students’ vocabulary mastery